IMPLEMENTASINYA PERKULIAHAN MATEMATIKA YANG HUMANISTIK PADA MAHASISWA KELAS 3T (TERDEPAN, TERPENCIL DAN TERTINGGAL) - Andri Anugrahana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is a qualitative descriptive study that reveals the implementation of humanistic mathematics lectures to the students from the Frontier (Terdepan), Remote (Terpencil) and Backward (Tertinggal) Areas (3T). The data were analyzed with qualitative data analysis techniques. This study aims to describe a model of humanistic mathematics lecture, explain the humanistic mathematics lectures, and explain the role of lecturers in humanistic mathematics lectures. The research subjects were students from the 3T area. 3T students are students from the most outermost regions in the territory of Indonesia. Mappi, Manokwari-Sorong, Timika, Asmat, and Mentawari Regencies. The results of the study stated that the humanistic mathematics learning model was using the PMRI approach. Steps of humanistic mathematics lectures: (1) introduction of the lectures, (2) understanding the material in groups, (3) groups interaction, (4) sharing opinions, (5) using the context in accordance with 3T students, (6) the freedom in searching for information, (7) students construct their own knowledge, (8) creating SANI : polite (santun), open (terbuka) and communicative (komunikatif) in lecturing, and (9) students were facilitated by positive, cooperative and open activities. The role of lecturers in humanistic mathematics lectures was as a facilitator and mediator.